2020
DOI: 10.1111/cmi.13191
|View full text |Cite
|
Sign up to set email alerts
|

Germ‐free and microbiota‐associated mice yield small intestinal epithelial organoids with equivalent and robust transcriptome/proteome expression phenotypes

Abstract: Intestinal epithelial organoids established from gut tissue have become a widely used research tool. However, it remains unclear how environmental cues, divergent microbiota composition and other sources of variation before, during and after establishment confound organoid properties, and how these properties relate to the original tissue. While environmental influences cannot be easily addressed in human organoids, mice offer a controlled assay-system. Here, we probed the effect of donor microbiota difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 102 publications
(143 reference statements)
2
40
0
Order By: Relevance
“…This expression profile is corroborated by our finding that levels of pro-caspase-11, but not pro-caspase-1, increased in IECs in response to IFN-γ treatment. In a recent publication by Hausmann et al, it was reported that TNF-α treatment of murine small intestine-derived enteroids also increased Casp11 expression [17]. Together with our findings, this suggests that although caspase-1 is sufficient to protect naïve IECs, as the infection proceeds, host inflammatory responses upregulate caspase-11 expression in IECs, leading to increased caspase-11 activity; the combined efforts of these two caspases form a multilayered innate defense that controls intracellular Salmonella burdens and protects the host from pathogen attack.…”
Section: Plos Pathogensmentioning
confidence: 99%
“…This expression profile is corroborated by our finding that levels of pro-caspase-11, but not pro-caspase-1, increased in IECs in response to IFN-γ treatment. In a recent publication by Hausmann et al, it was reported that TNF-α treatment of murine small intestine-derived enteroids also increased Casp11 expression [17]. Together with our findings, this suggests that although caspase-1 is sufficient to protect naïve IECs, as the infection proceeds, host inflammatory responses upregulate caspase-11 expression in IECs, leading to increased caspase-11 activity; the combined efforts of these two caspases form a multilayered innate defense that controls intracellular Salmonella burdens and protects the host from pathogen attack.…”
Section: Plos Pathogensmentioning
confidence: 99%
“…Our results highlight a previously unappreciated dynamic behavior of intestinal epithelia. epithelium (6,9). Organoid models have for these reasons become attractive tools for physiological studies of gut infection (25,(29)(30)(31)(32).…”
Section: Significancementioning
confidence: 99%
“…As a system to sense mucosal intrusions, IECs express pattern recognition receptors (PRRs) [e.g., Toll-like receptors associated with cell membranes (6), and Nod-like receptors (NLRs) that form inflammasomes in the cytosol] (7)(8)(9). Epithelial recognition of pathogens through PRRs elicits a panel of countermeasures, including production of proinflammatory cytokines, chemokines, lipids (10)(11)(12)(13), secretion of antimicrobial peptides (11,14), and the death and expulsion of infected IECs into the lumen (12,15,16).…”
mentioning
confidence: 99%
“…However, the finding that the transcriptome and proteome of small intestinal stem cell-derived organoids from SPF and GF mice co-cluster (Hausmann et al, 2020), would argue against this possibility although in this study no account was made for any possible differences in EEC distribution or number. Indeed, whereas our analysis relied on cellular comparisons of EEC in epithelial cell monolayer cultures versus in intact tissue, other studies have used single or multi-omicsbased approaches in comparative studies (Lindeboom et al, 2018;Beumer et al, 2020;Hausmann et al, 2020;Ohki et al, 2020). Other possible confounding factors include comparing EECs in two-dimensional epithelial cell monolayers versus stem cell-derived three-dimensional organoids, other methodological differences including the age of the mice used, where in the small intestine crypts are obtained from Fuller et al (2012), the duration of culture, and the type and concentrations of growth and differentiation factors used.…”
Section: Discussionmentioning
confidence: 70%
“…Our contradictory findings may relate to our use of GF mice, as SPF mice are the usual source of intestinal crypts (Petersen et al, 2014;Roberts et al, 2019). However, the finding that the transcriptome and proteome of small intestinal stem cell-derived organoids from SPF and GF mice co-cluster (Hausmann et al, 2020), would argue against this possibility although in this study no account was made for any possible differences in EEC distribution or number. Indeed, whereas our analysis relied on cellular comparisons of EEC in epithelial cell monolayer cultures versus in intact tissue, other studies have used single or multi-omicsbased approaches in comparative studies (Lindeboom et al, 2018;Beumer et al, 2020;Hausmann et al, 2020;Ohki et al, 2020).…”
Section: Discussionmentioning
confidence: 71%